The Effect of Psychoeducation on Reducing Anxiety in Elderly with Hypertension - Mayra Rizky Susanti; Wachidah Yuniartika (Indonesian Journal of Global Health Research, 2025)
Anxiety is a common issue among elderly individuals with hypertension, which can negatively impact their overall well-being. Psychoeducation is considered an effective intervention to reduce anxiety levels. Objective: This study aims to examine the effect of psychoeducation on reducing anxiety in elderly individuals with hypertension.Method: A pre-experimental study with a one-group pre-test and post-test design was conducted. The study used purposive sampling, involving 10 respondents who experienced anxiety. Data were analyzed using the Wilcoxon test Results: The findings indicate a significant difference in anxiety levels between the pre-test and post-test, with a p-value of 0.003 (p < 0.05).Conclusions: Psychoeducation has a significant effect on reducing anxiety in elderly individuals with hypertension.